Musik Sebagai Media Gerakan Sosial Baru(Studi Kualitatif Deskriptif dengan Menggunakan Teori Interaksionisme Simboliktentang Grup Musik Merah Bercerita) - TAMIMI, REZA ULVA, Fajar Junaedi, S.Sos. M.Si (2017)
Music is delivery medium of messages, where elements of the song, music instrument, tone and tempo became a symbolic language in the delivery of the message. And lyrics became the core of the symbolic language, in addition to its aesthetical meaningful music can be dialectic with social reality. Also can be used as a simple language to understand the reality it self. This study aims to determine how the "Merah Bercerita" music group symbolic behaviour in carrying the social human rights movements. By using symbolic interactionism theory approach, the researchers will be easier to examine how social human rights movements manifested in symbolic behavior of Merah Bercerita music group. The method used is qualitative data collection techniques broadly divided into two parts, the first primary data, and the second is secondary data. In collecting the data, this study using the technique of in-depth interviews and observation using unstructured observation, while the subject of this study was the personnel of "Merah Bercerita" music group. These results indicate that the social human rights movements conducted by "Merah Bercerita" through the medium of music can be said to be effective, other than being an entertainment music media can be used as a medium of resistance and criticism by Merah Bercerita, with the approach of symbolic interactionism researchers found symbolic behavior in which "Merah Bercerita" using media such as lyrics , music, tones, images that became a symbolic language in message delivery.